2014
DOI: 10.1111/jan.12483
|View full text |Cite
|
Sign up to set email alerts
|

A comparative review of nurse turnover rates and costs across countries

Abstract: A significant proportion of turnover costs are attributed to temporary replacement, highlighting the importance of nurse retention. The authors suggest a minimum dataset is also required to eliminate potential variability across countries, states, hospitals and departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
258
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(268 citation statements)
references
References 22 publications
2
258
0
8
Order By: Relevance
“…Reasons given for this include: poor job satisfaction and commitment to their employer, lack of socialisation, emotional exhaustion, dissatisfaction with workplace environments, poor interpersonal relationships with staff, and having witnessed and/or experienced bullying. In addition to the personal costs for the individual nurse, the financial costs associated with attrition are significant, ranging between $26,652 to $48,970 in Canada and Australia respectively (Duffield et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Reasons given for this include: poor job satisfaction and commitment to their employer, lack of socialisation, emotional exhaustion, dissatisfaction with workplace environments, poor interpersonal relationships with staff, and having witnessed and/or experienced bullying. In addition to the personal costs for the individual nurse, the financial costs associated with attrition are significant, ranging between $26,652 to $48,970 in Canada and Australia respectively (Duffield et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[26,27] Raup I et al showed that transformational leadership was associated with lower staff turnover trends in comparison with other leadership styles. [3,27] More importantly, studies pointed out that the nurses' intent to leave their workplace and the subsequent organizational turnover are influenced more by supervisors than by co-workers, which can be due to the increased importance of mentoring in the nursing field. [10,28] Studies have also specifically discussed the importance of teams and collaboration at the workplace to motivate employees to stay with an organization or within the nursing profession.…”
Section: Social Work Environmentmentioning
confidence: 99%
“…[1] Evidence suggests that increased nurse turnover results in decreased patient access, patient safety and quality of care leading to adverse patient outcomes. [2][3][4][5] Simultaneously, nurse turnover also has a spillover effect on the remaining RNs by increasing their workload and job stress which leads to burnout and subsequently to further turnover. [2,6] Nurse turnover can also adversely impact health care organizations' bottom line through higher recruitment and replacement costs.…”
Section: Introductionmentioning
confidence: 99%
“…The cost of replacing each 'lost' nurse has been calculated at US$48,790 in Australia, $26,652 in Canada, and $20,561 in the United States. [4] Turnover rates are generally much higher among new hires and for recent nursing graduates. [5] Jones, [6,7] in a study of nursing turnover costs, characterizes nursing turnover as the process whereby nursing staff leave or transfer within an institutional environment.…”
Section: Introductionmentioning
confidence: 99%